Acute effects of high intensity training on cardiac function: a pilot study comparing subjects with type 2 diabetes to healthy controls - Ness, Henning O.; Ljones, Kristine; Gjelsvik, Randi H.; Tjønna, Arnt Erik; Malmo, Vegard; Nilsen, Hans Olav; Hollekim-Strand, Siri Marte; Dalen, Håvard; Høydal, Morten Andre (Scientific reports, 2022)
This study evaluated acute cardiac stress after a high-intensity interval training session in patients with type 2 diabetes (T2D) versus healthy controls. High intensity aerobic exercise was performed by 4 × 4-min intervals (90–95% of maximal heart rate), followed by a ramp protocol to peak oxygen uptake. Echocardiography was performed before and 30 min after exercise. Holter electrocardiography monitored heart rhythms 24 h before, during, and 24 h after the exercise. Left atrial end-systolic volume, peak early diastolic mitral annular velocity, and the ratio of peak early to late diastolic mitral inflow velocity were reduced by approximately 18%, 15%, and 31%, respectively, after exercise across groups. Left ventricular end-diastolic wall thickness was the only echo parameter that significantly differed between groups in response to exercise. The T2D group had a rate of supraventricular extrasystoles per hour that was 265% greater than that of the controls before exercise, which remained higher after exercise. A single exhaustive exercise session impaired left ventricular diastolic function in both groups. The findings also indicated impaired right ventricular function in patients with T2D after exercise. ClinicalTrials.gov Identifier: NCT02998008.